2018
DOI: 10.12691/jfnr-6-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and α-Glucosidase Inhibitory Activity of Polyphenols in Peel and Core from Five Different Pear Varieties

Abstract: This study was performed to compare polyphenol content, DPPH radical scavenging activity and αglucosidase inhibitory activity in peel, core and pulp of five different pear cultivars. Oligomeric polyphenols were the main polyphenols in core, which exhibited greater polyphenols, DPPH radical scavenging activity, and αglucosidase inhibitory activity, compared to peel and pulp. For the peel, Japanese pears including Yasato, 20-Seki and Shinko pear contained relatively more polyphenol content and α-glucosidase inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
3
0
0
Order By: Relevance
“…It indicated that more highly polymerized polyphenols exhibited more potent inhibitory activities on α-glucosidase. Consistent with this, we also observed that oligomeric and polymeric polyphenols exhibited stronger α-glucosidase inhibitory activity than monomeric polyphenols in pears and scarlet runner beans [18,21]. These results may be explain why seed polyphenols had the strongest inhibitory activity than the other parts on digestive enzymes.…”
Section: Polyphenol Fractionssupporting
confidence: 88%
See 1 more Smart Citation
“…It indicated that more highly polymerized polyphenols exhibited more potent inhibitory activities on α-glucosidase. Consistent with this, we also observed that oligomeric and polymeric polyphenols exhibited stronger α-glucosidase inhibitory activity than monomeric polyphenols in pears and scarlet runner beans [18,21]. These results may be explain why seed polyphenols had the strongest inhibitory activity than the other parts on digestive enzymes.…”
Section: Polyphenol Fractionssupporting
confidence: 88%
“…Polyphenol content was much higher than in the flesh [17]. We also found peel of European pears and Japanese pears that peel had higher polyphenol content than those of flesh [18]. Moreover, Leontowicz et al [17] reported that polyphenol content was 1.07 ± 0.1 mg/g in apple peel and 0.62 ± 0.1 mg/g in apple flesh.…”
Section: Polyphenol Contentsupporting
confidence: 56%
“…The same phenolic subgroups were identified in the pulp, with the exception of flavonols. The content of all analyzed polyphenol compounds was higher in pear peel (574.93 mg kg −1 ) than in pulp (36.86 mg kg −1 ), which is in accordance with earlier reported results [10,33]. Traditional pear cultivars had higher total phenols in both peel and pulp than the commercial 'Président Drouard', with the exception of cultivars 'Takiša' and 'Ahmetova' (Table 4).…”
Section: Phenolics Compositionsupporting
confidence: 91%